Targeting HMGB1 in endothelial cells reverses heme-induced SIRS after radiofrequency ablation of hepatic hemangioma - Yao, Changyu; Zhou, Ying; Yu, Liuyang; Xu, Li; Wu, Shilun; Gao, Ruize; Hou, Yirui; Sun, Wenbing; Gao, Jun; Wang, Shaohong (Frontiers in Immunology, 2025)
BackgroundAlthough radiofrequency ablation (RFA) is a safe and effective treatment for hepatic hemangiomas, post-RFA systemic inflammatory response syndrome (SIRS) frequently occurs. The role of high-mobility group box 1 (HMGB1) in endothelial cell pyroptosis and SIRS induction following RFA in hepatic hemangiomas remains unexplored.MethodsIn vitro, the levels of interleukin (IL)-1β, IL-18, and pyroptosis markers, such as GSDMD-N and Casp1 p20, were measured in human umbilical vein endothelial cells (HUVECs) after heme administration. In vivo, an orthotopic liver hemangioma mouse model was established, and RFA was performed to evaluate the levels of IL-1β and IL-18, wet-to-dry lung ratio, and inflammation score. In addition, hemopexin and glycyrrhizin were used to investigate the impact of HMGB1 on heme-induced SIRS post-RFA in hepatic hemangioma mice.ResultsHeme induced elevated levels of IL-1β and IL-18, endothelial cell death in vitro, and increased wet-to-dry lung ratio and inflammation score in vivo. These effects were rescued with the administration of heme-binding protein hemopexin, indicating the role of heme in inducing SIRS and pyroptosis post-RFA of hepatic hemangioma. HMGB1 participates in heme-induced SIRS in mice by regulating HMGB1/nod-like receptor family pyrin domain-containing 3 (NLRP3) pathway through reactive oxygen species (ROS). Treatment with hemopexin or the HMGB1 inhibitor glycyrrhizin reversed heme-induced SIRS after RFA of hepatic hemangioma in mice.ConclusionsCollectively, we demonstrated that heme induces SIRS through the ROS/HMGB1/NLRP3 pathway-regulated endothelial cell pyroptosis in mice, and hemopexin, a heme scavenger, and glycyrrhizin, a HMGB1 inhibitor, may be the potential strategies for further study for SIRS following the RFA of hepatic hemangioma for the first time.